Education, health literacy, and inequity in access to transplantation: findings from the ATTOM cohort study. (November 2017) - Taylor, Dominic M; Fraser, Simon D S; Ravanan, Rommel; Roderick, Paul; ,
Abstract: Background: The optimal treatment for most people with kidney failure is kidney transplantation, but donor organs are limited. The pathway to living-donor or deceased-donor kidney transplantation entails multiple clinician–patient interactions, likely to require adequate health literacy. The Access to Transplant and Transplant Outcome Measures (ATTOM) study identified inequity in access to transplantation by educational level. We tested the hypothesis that low health literacy promotes inequity by acting as a mediator between reduced education and transplantation. Methods: The ATTOM cohort study recruited incident dialysis patients aged 18–75 years, who were able to provide informed consent, from all 72 kidney units in the UK from Dec 1, 2011, to Sept 30, 2013]. This mediation analysis concerned the exposure (no educational qualifications vs any), prospective outcomes (time to being added to the deceased-donor transplant waiting list and time to living-donor transplantation, censored at 2 years), the mediator (health literacy as judged by Single Item Literacy Screener, a validated, self-reported health literacy screening measure) and covariates (age, ethnicity, and comorbidity by Charlson index). Effect sizes were calculated for education on health literacy, health literacy on being added to the transplant waiting list and living-donor transplantation, and for education on being added to the waiting list and living-donor transplantation, all adjusted for the covariates. These effect sizes were used to calculate the total effect of education on being added to the transplant list and transplantation and the indirect effect mediated by health literacy. Weibull Accelerated Failure Time models were used. Ethics approval was given by Cambridge Research Ethics Committee. Findings: 2463 patients were included. The total effect of low educational level was to increase the time to being added to the transplant waiting list by 22% (time to event ratio 1·22, 95% CI 1·02–1·48) and time to living donor transplant by 47% (1·47, 1·04–2·08). The indirect effect mediated by health literacy accounted for 35% and 30%, respectively. Interpretation: Our findings show that health literacy mediates a substantial proportion of the effect of low educational level on reduced access to the deceased-donor transplant waiting list and to living donor transplantation. Interventions to improve equity of transplantation should account for the health literacy skills needed for patients to take part in shared decision making. Funding: ATTOM was funded under National Institute for Health Research Programme Grants for Applied Research (RP-PG-0109-10116).